Urinary neutrophil gelatinase-associated lipocalin to predict acute kidney injury in children with critical illness - Fajri, Rizky; Sovira, Nora; Haris, Syafruddin; Dimiati, Herlina; Bakhtiar, Bakhtiar; Amna, Eka Yunita (Paediatrica Indonesiana, 2025)
Background Acute kidney injury (AKI) can increase mortality in children with critical illness. Urinary neutrophil gelatinase-associated lipocalin (uNGAL) is a biomarker for early prediction of AKI in children. Objective To determine the diagnostic value of uNGAL as a predictor of AKI in children with critical illness. Methods This observational cross-sectional study was conducted in the Emergency Room, Pediatric Intensive Care Unit, and Pediatric Ward of Zainoel Abidin Public Hospital, Banda Aceh, Indonesia, between August and December 2023. Subjects were 40 children aged 1 month to 18 years with critical illness. uNGAL levels were measured on the first day of admission. Blood urea and creatinine levels were measured on the first and third days of admission. We calculated the diagnostic sensitivity and specificity of uNGAL to predict AKI. The optimal uNGAL cut-off point for this purpose was determined using receiver operating characteristic (ROC) curve analysis. Result In the majority of patients (29/40; 72.5%) critical illness occurred at the ages of 5 to 18 years. The most common primary diseases were central nervous system disorders in 14/40 (35%) patients, gastrointestinal infection in 6/40 (15%) patients, and malignancy in 5/40 (12.5) patients. Median uNGAL levels were significantly elevated in subjects with renal impairment [17.37 (range 6.13-29.70) ng/mL] compared to those with normal renal function [4.87 (range 0.32-29.49) ng/mL] (P=0.0001). The optimal uNGAL cut-off point was >9.99 ng/mL, with an AUC of 0.842, 81% sensitivity, and 78.9% specificity to predict AKI. The OR of AKI in children with uNGAL levels >9.99 ng/mL was 10.66 (95%CI 2.30 to 49.30; P=0.003). Conclusion Urinary neutrophil gelatinase-associated lipocalin (uNGAL) can be used as a predictor of acute kidney injury in children with critical illness.